Pengaruh Terapi Bermain terhadap Kecemasan Anak pada Masa Hospitalisasi - Adolfina Tandilangan; Jani Rante Tasik; Turena Indah Julianty; Meyke Tiku Pasang; Ricky Riyanto Iksan (Universitas Malahayati, 2023)
ABSTRACT The results of the 2015 World Health Organization (WHO) survey, almost 87% of children experienced hospitalization. The results of the Basic Health Research survey found that the average data of children who were hospitalized in hospitals throughout Indonesia was 2.8% of the total number of children of 82,666 people. The aim of the study was to determine the effect of play therapy on children's anxiety during the hospitalization period. Research method: in this study using a literature review by using a search through Google Schoolar, and pubmed. From the 5 journals that have been reviewed, that there is an effect of play therapy on children's anxiety during the hospitalization period. The conclusion is that play therapy is an alternative non-pharmacological therapy that can affect children's anxiety during hospitalization. Keywords: Play Therapy, Child Anxiety, Hospitalization ABSTRAK Hasil survei World Health Organization (WHO) tahun 2015, Hampir 87% anak mengalami perawatan dirumah sakit. Hasil survei Riset Kesehatan Dasar (Riskesdas,2018) didapatkan data rata-rata anak yang menjalani rawat inap di rumah sakit di seluruh Indonesia adalah 2,8% dari total jumlah anak 82.666 orang. Tujuan penelitian untuk mengetahui adanya pengaruh terapi bermain tehadap kecemasan anak pada masa hospitalisasi. Metode penelitian : dalam penelitian ini menggunaan kajian literature review dengan menggunakan pencarian melalui Google Schoolar, dan pubmed. Dari ke 5 jurnal yang telah di review, bahwa Ada Pengaruh Terapi Bermain Terhadap Kecemasan Anak Pada Masa Hospitalisasi. Kesimpulan yang didapat bahwa terapi bermain sebagai salah satu terapi alternative non farmakologi yang dapatberpengaruh terhadap kecemasan anak pada masa hospitalisasi. Kata Kunci: Terapi Bermain, Kecemasan Anak, Hospitalisasi